Analysis of an N-policy GI/M/1 queue in a multi-phase service environment with disasters - Jiang, Tao; Ammar, Sherif I.; Chang, Baoxian; Liu, Liwei (Zielona Góra: Uniwersytet Zielonogórski)
This paper investigates an N-policy GI/M/1 queue in a multi-phase service environment with disasters, where the system tends to suffer from disastrous failures while it is in operative service environments, making all present customers leave the system simultaneously and the server stop working completely. As soon as the number of customers in the queue reaches a threshold value, the server resumes its service and moves to the appropriate operative service environment immediately with some probability. We derive the stationary queue length distribution, which is then used for the computation of the Laplace-Stieltjes transform of the sojourn time of an arbitrary customer and the server`s working time in a cycle. In addition, some numerical examples are provided to illustrate the impact of several model parameters on the performance measures.
Keywords: N-policy; GI/M/1 queue; multi-phase service environment; disasters; sojourn times